CONSENSUS IN TAFSIR ON THE MEANING OF AL-FATĀ IN SURAH AL-KAHF [18]:60 A MODERN AND CONTEMPORARY TAFSIR PERSPECTIVE - Fitri Meliani (Ma'had Aly As'adiyah Sengkang, 2025)
AbstractThis paper examines Ijma’ fi al-Tafsir regarding the meaning of al-fatā in QS al-Kahfi [18]:60 from the perspective of modern–contemporary exegetes. Using library research with a descriptive–analytical approach, it analyzes five tafsir works: al-Wasīṭ (Tantawi), Tafsir Asy-Sya‘rawi, Tafsir al-Azhar (Hamka), al-Mishbah (Quraish Shihab), and Zahratu al-Tafāsīr (Abu Zahrah). The results identify two typologies: (1) citing and accepting Ijma’ fi al-Tafsir, as done by Tantawi, Asy-Sya‘rawi, Hamka, and Quraish Shihab, who affirm al-fatā as Yūsha‘ bin Nūn based on authentic hadiths and the view of the majority; and (2) not explicitly citing Ijma’, as in Abu Zahrah’s interpretation, which maintains the general meaning of the term. These findings highlight the dynamic application of Ijma’ fi al-Tafsir in the modern–contemporary era, shaped by each exegete’s methodological framework and interpretive orientation. Keywords: Ijma’ fi al-Tafsir, al-fatā, QS al-Kahfi.